Effects of imatinib on glycemic and lipid profiles: a retrospective cohort study. Issue 9 (29th July 2022) - Markovits, Noa; Kurnik, Daniel; Friedrich, Carmel; Gueta, Itai; Halkin, Hillel; David, Sara; Lomnicky, Yossi; Topol, Yael; Tirosh, Amir; Loebstein, Ronen
Abstract: Despite a favorable effect of imatinib on glucose metabolism in animal models, human reports are inconsistent. We retrospectively studied the long-term effect of imatinib on fasting plasma glucose (FPG), glycated hemoglobin (HbA1C), LDL-cholesterol (LDL), and triglycerides (TGs) in a large HMO cohort of patients initiating therapy. In patients with diabetes ( n  = 118), significant reductions in HbA1c (0.53%, IQR 0.09, 1.19; p  < .001) and FPG (10.2 mg/dL, IQR −3.5, 32.2; p  < .001), independent of demographics and of glucose-lowering drugs utilization, were observed during the first year of imatinib treatment. Significant reductions in LDL (17.8 mg/dL, IQR −1.3, 34.0; p  < .001) and TG (25.0 mg/dL, IQR −2.3, 58.3; p  < .001), also independent of demographics and of statin utilization, were evident in the entire cohort ( n  = 611) during the first imatinib year. All reductions persisted during the second treatment year. To conclude, imatinib is associated with durable metabolic benefits, which may guide TKI choice in patients with cardiovascular co-morbidities.